EFEKTIFITAS PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA - Wiarti, July (UIR Law Review, 2023)
Cases of criminal acts of corruption continue to increase every year and so it appears that there are problems in law enforcement. Lawrence M. Friedman said there are three components that can be studied to see whether good law enforcement has been implemented or whether a law is effective or not, namely legal substance, legal structure and legal culture. Therefore, it is necessary to study these three components regarding criminal acts of corruption to see how the law is enforced. The method used is normative legal research which is based on secondary data. Based on these three components, it was indeed found that there were problems in law enforcement regarding criminal acts of corruption. In terms of legal substance, the existing provisions are no longer in accordance with the current situation, for example in terms of types of criminal acts of corruption that have experienced development and provisions that still cause problems in their implementation. In terms of legal structure, several institutions have been involved, including KPK, but KPK's performance is far from good, in fact ICW said KPK's performance is still poor. Finally, in terms of legal culture, society still finds it difficult to let go of the habit of corrupt practices, as does law enforcement.